Buying from Local Providers: The Role of Governance Preferences in Assessing Performance Information. (19th April 2022) - Lerusse, Amandine; Van de Walle, Steven
Abstract: Governance preferences influence how public officials process performance data about service providers. Based on motivated reasoning theory, we examine the extent to which local delivery preferences—preferences for contracting with local service providers over contracting with non‐local ones—influence public managers' and politicians' interpretation of performance data. We firstly expect public officials to misinterpret evidence that contradicts their local delivery preferences and we, secondly, hypothesize that politicians are more prone to biases than public managers are. We test these hypotheses by conducting a randomized survey experiment among 4, 000 public officials in Belgium. The results indicate that public officials tend to show a bias for local providers, but not for non‐local providers. Yet, we found no significant differences between politicians and public managers. Our study provides new evidence about the influence of governance preferences on the interpretation of performance information, and calls into question its effective use by politicians and public managers.